2020
DOI: 10.1093/gerona/glaa003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinically Meaningful Changes in Measures of Frailty

Abstract: Background To determine the clinically meaningful changes and responsiveness of widely used frailty measures. Methods We analyzed data from a prospective cohort study of 1,135 community-dwelling older adults who underwent assessments of frailty and health-related quality of life using the EuroQol-5D at baseline and 1 year later. Frailty measures included deficit-accumulation frailty index (FI); frailty phenotype; Fatigue, Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 27 publications
3
47
2
Order By: Relevance
“…Previous work using cross‐sectional data estimated that deficit accumulation occurs at a rate of 3% per year on a logarithmic scale 19 . A recent study suggested that a change in FI of 0.03 was sensitive to detect small changes in EuroQol‐5D, a global measure of health status 15 . Another study compared frailty measurements from different time points, concluding that the most recent frailty measurement was a better predictor of mortality 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work using cross‐sectional data estimated that deficit accumulation occurs at a rate of 3% per year on a logarithmic scale 19 . A recent study suggested that a change in FI of 0.03 was sensitive to detect small changes in EuroQol‐5D, a global measure of health status 15 . Another study compared frailty measurements from different time points, concluding that the most recent frailty measurement was a better predictor of mortality 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Change in frailty was calculated as the difference in FI from Round 1 to Round 2; thus, a positive change indicates increasing deficits and worsening frailty. Prior literature on change in FI has suggested that the minimally clinically important difference in FI is 0.03 15 . However, some studies have also examined change as a percentage of baseline frailty level 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Health deficits accumulate at a slower rate in mid-life than at older ages [27] and frailty measured in younger populations might be clinically and biologically different from that measured in older populations[l]. Nonetheless, our measure of frailty is particularly suited to mid-life because it has demonstrated good construct validity at this life stage[45] and it provides a continuous score of fitness to frail [24] allowing detection of small differences in health compared to other measures[26]. Finally, as with all long-term studies, attrition occurred over time.…”
Section: Discussionmentioning
confidence: 99%
“…This index considers the accumulation of health-related deficits[24,25], and is a validated and commonly used approach to operationalising frailty. Compared with other frailty measures, the FI is more sensitive to small changes in health status[26] making it particularly suitable for examining frailty in mid-adulthood, a life-stage when health deficits are accumulating at a slower rate than at older ages [27].…”
mentioning
confidence: 99%
“…We evaluated depressive mood using the Korean version of the CES‐D (range: 0–60) and defined depression as a CES‐D score ≥21 24,25 ; cognitive function using the Korean MMSE 26 ; and malnutrition using the Mini‐Nutritional Assessment Short Form (MNA‐SF) (range: 0–14). Frailty was assessed according to the frailty phenotype scale (range: 0–5) based on unintentional weight loss, exhaustion, inactivity, slow gait speed, and weak grip strength, 27 as well as a deficit‐accumulation frailty index (range: 0–1) based on 43 health deficit items (38 self‐reported items and five performance test items) 28‐30 …”
Section: Methodsmentioning
confidence: 99%